Insya’ Tholabi Dalam Surat Al-MujaDilah - Qolby, Darul (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2017)
This journal entitled al-Insya 'at -Ta alabiy fi Surati al-Mujadilah (Dirasah Tahliliyyah Tada wuliyyah). Writing this journal on the back of many found sentences, assuming that the sentence does not work as the original. But in other circumstances, some sentences have other functions that can be understood in context when the utterance is uttered. Therefore, the researcher is interested to study and examine the letter of al-Mujadilah by asking two questions formulation, firstly, how many verses are not conventionally interpreted in the letter of al-Muja> dilah ? Second, what verses that are not conventionally interpreted in surat al-Mujadilah? Third, what is the function of the verse that is not conventionally interpreted in surat al-Mujadilah? The purpose is to know how many numbers, sentences and sentence functions that contain speech acts in the letter al-Mujadilah. The theory that researchers use and proposed is a pragmatic theory that was promoted by Austin to act speech because only this theory that can dissect and describe the function or intention contained in the sentence that contains not functioned as it should. This research is a research library (library research) with materials or reference sources obtained from the library. The data analysis is done by qualitative method and presented with descriptive analysis method, so that can know the final result of research. Abstract: Insya 'at -Ta alabiy,  al-Mujadilah, Tinda Tutur